Cloning, sequencing, expression, and complementation analysis of the Escherichia coli K1 kps region 1 gene, kpsE, and identification of an upstream open reading frame encoding a protein with homology to GutQ. - Cieslewicz, M J (1993)
The kps locus for polysialic acid capsule expression in Escherichia coli K1 is composed of a central group of biosynthetic neu genes, designated region 2, flanked on either side by region 1 or region 3 kps genes with poorly defined functions. Chromosomal mutagenesis with MudJ and subsequent complementation analysis, maxicell and in vitro protein expression studies, and nucleotide sequencing identified the region 1 gene, kpsE, which encodes a 39-kDa polypeptide. Polarity of the kpsE::lacZ mutation suggests an operonic structure for region 1. KpsE is homologous to putative polysaccharide-translocation components previously identified in Haemophilus influenzae type b and Neisseria meningitidis group B. An open reading frame upstream of kpsE encodes a 35-kDa polypeptide with homology to GutQ, a putative ATP-binding protein of unknown function encoded by gutQ of the glucitol utilization operon. Whether expression of the gutQ homolog as the potential first gene of region 1 is required for polysialic acid synthesis or localization is presently unknown.